Thin films growth by PIIID technique from hexamethyldisilazane/argon mixture - Kodaira, F. V.P. [UNESP] (2015)
Plasma polymer thin films are pinhole-free and have also a high cross-linked structure. These kinds of films are insoluble inmild acids and bases and present good adhesion on differentmaterials. These features make the films relevant for industrial applications and are used in different fields such as electronics, mechanics, biomedics, electrics, protective coatings and others. The plasma polymer hexamethyldisilazane/argon films (ppHMDSN/Ar) were deposited on substrates which were placed between two stainless steel parallel plate electrodes fed by a radio-frequency source operated at 13.56 MHz and 50 W at a total pressure (HMDSN and argon) of 80 mTorr. The negative bias of 10 kV and 10 Hz pulse were used for ion implantation. The structural characterization of the films was done by FTIR spectroscopy. The contact angle for water was of approximately 98- and the surface energy of 30 mJ/m2 which represents a hydrophobic surface, measured by goniometric method. The refractive index of these materials presents values from 1.56 to 1.64 measured by ultraviolet-visible technique. The thickness of the sampleswasmeasured by profilometry and showed values from96 to 210 nmfor different deposition conditions resulting in deposition rates from 4.8 to 10.5 nm/min. Hardness values ranging from 0.9 to 2.6 GPa were found for the filmsmeasured by nanoindentation technique.